Transnational family support and perspectives from family members back home: a pilot study in Kisumu, Kenya - Lisa Merry; Dominic Mogere; Dan Odindo; Nancy Edwards (Inishmore Laser Scientific Publishing Ltd, 2019)
# Background Transnational family support as a resource for migrants is understudied, particularly from the perspective of those providing support from a distance. This pilot study aimed to determine the feasibility of conducting transnational research and gathering data from family members back home using communication technology. Preliminary data on the experience of providing transnational support to migrant family members living abroad, were also collected. # Methods We conducted a small, qualitative descriptive study in Kisumu, Kenya. A convenience, purposive sample of six men and three women, who self-identified as providing support to migrant family members living in another country were recruited. Data were collected via semi-structured interviews through Skype phone calls with a researcher in Canada. # Results Participants had various relationships (sibling, spouse, parent, uncle, cousin) to those who migrated; family members lived in the UK, US and Canada. Gathering data virtually was feasible, although there were some practical challenges and communication barriers. Interviews revealed that participants were open to share and highlighted the importance of obtaining perspectives from different family members and asking a variety of questions to elicit both positive and negative experiences. The risk of sensitive topics causing distress, raises some ethical concerns about how researchers may adequately respond and provide support from a distance. The preliminary data collected on the experiences of providing transnational family support showed that participants provided financial, emotional, spiritual and practical support. Support varied with time, with help being more intense during early resettlement and in times of financial difficulty; gender, relationship and closeness seemed to shape the nature and extent of support given. Participants mostly felt positive about their family members' migration although they also disclosed experiences of conflict and tension, which were in part due to the support-giving context. # Conclusions Family members back home are willing to engage in transnational research and using communication technology is an efficient and logistically feasible approach for gathering data from these participants. Including family members' back home in research yields informative data on transnational family support.